Effects of avocado seed extract in different tris-extenders on sperm and oxidative stress parameters of West African Dwarf goat spermatozoa during vitrification - Daramola, James Ola; Onanuga, Oluwakemi Dayo; Abioja, Monsuru Oladimeji; Adeleke, Mathew; Olowofeso, Olajide; Oke, Oyegunle Emmanuel; Adekunle, Ezekiel Oluwafemi; Sorongbe, Taiwo Amidu; Iyanda, Olayinka Ayobami (Journal of Agricultural Sciences (Belgrade), 2016)
Abstract: Effects of avocado seed extract (ASE) in different tris-extenders on sperm and oxidative stress parameters of West African Dwarf (WAD) goat during vitrification were evaluated. Semen samples were diluted with different levels of ASE (0, 5, 10, 15 and 20 mL/100 mL of diluent) each in tris citric acid (TCA), tris sodium phosphate (TSP) and tris sodium citrate (TSC) extenders while Tris-extender without citric acid, sodium phosphate and sodium citrate served as control. Diluted semen samples were vitrified and stored for 30 days. The results showed higher (P<0.05) sperm motility in TCA extenders at 10 % 15 % and 20 %, and TSP extender at 20 % ASE. Higher (P<0.05) acrosome integrities were observed in the different tris-extenders at 15 % and 20 % ASE. TCA, TSP and TSC extenders had higher (P<0.05) membrane integrities at 10 %, 15 % and 20 % ASE. TSP extenders had higher (P<0.05) live sperm at 20 % ASE. TCA extenders had higher acrosome reaction while TSP at 20% ASE and TSC at 15% and 20% of ASE had higher sperm capacitation. TCA extender at 20% ASE had reduced malondialdehyde (MDA) concentrations while higher acrosin activities were observed at 20% ASE in TCA extender (P<0.05). The findings indicated that 20% ASE in the tris-extenders improved sperm and oxidative stress parameters and the tris-extenders is ranked best in this order: TCA > TSP > TSC.